Gambaran Karakteristik Jenazah Terkonfirmasi Positif COVID-19 di RSUD dr. Doris Sylvanus - Darmawan, Muhammad Riza (Indonesian Journal of Legal and Forensic Sciences (IJLFS), 2024)
CoronaVirus Disease-2019 (COVID-19) is an infectious disease caused by Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2). SARS-CoV-2 is a novel coronavirus that has been never identified in humans. dr. Doris Sylvanus Hospital is one of the COVID-19 referral hospitals, especially in Central Borneo. Objectives of this study is aim to determine the characteristics of confirmed COVID-19 corpses based on age, gender, and comorbid diseases in confirmed COVID-19 corpses at dr. Doris Sylvanus Hospital. Method used in this study is descriptive observational with a retrospective approach, data was obtained through medical records of corpses who died confirmed with COVID-19. The result from this study is 338 corpses were confirmed with COVID-19, dominated by group age 55-64 years (33%), men (59%), and diabetes mellitus as the highest comorbid disease (19.71%). This research concluded that the corpses confirmed with COVID-19 at dr. Doris Sylvanus Hospital were dominated by group age of 55-64 years, men, with diabetes mellitus as comorbid disease. Keywords: COVID-19; Corpses; Characteristics; dr. Doris Sylvanus Hospital